2016
DOI: 10.1037/a0039966
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of the feasibility of using ecological momentary assessment to study teacher stress: Objective and self-reported measures.

Abstract: There is a lack of comprehensive research on Ecological Momentary Assessment (EMA) feasibility to study occupational stress, especially its long-term sustainability. EMA application in education contexts has also been sparse. This study investigated the feasibility of using EMA to study teacher stress over 2 years using both objective compliance data and a self-reported feasibility survey. It also examined the influence of individual and school factors on EMA feasibility. Participants were 202 sixth through ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 25 publications
1
7
0
1
Order By: Relevance
“…These results are congruent with the ones found by Renshaw, Long, and Cook (2015), which reveal that the higher the age the bigger the emotional exhaustion. Similar results were found by McIntyre et al (2015), who refer that younger teachers showed higher stress levels than the older ones. Our results indicate no significant differences between the teachers aged 26-44 years, who present higher medium levels in all PsyCap dimensions.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…These results are congruent with the ones found by Renshaw, Long, and Cook (2015), which reveal that the higher the age the bigger the emotional exhaustion. Similar results were found by McIntyre et al (2015), who refer that younger teachers showed higher stress levels than the older ones. Our results indicate no significant differences between the teachers aged 26-44 years, who present higher medium levels in all PsyCap dimensions.…”
Section: Resultssupporting
confidence: 78%
“…Nevertheless, this imbalance may emerge because the situation truly requires excessively from the individual. Several studies (e.g., McIntyre et al, 2015;Tomioka, Morita, Saeki, Okamoto, & Kurumatani, 2011) state that not only stress has a direct effect but it also has an indirect effect on depression and generates particular psychological responses. …”
Section: Stressmentioning
confidence: 99%
“…Participants also always had the option to snooze the notification: if they dismissed it (swiped it away), it reappeared after 15 min. Previous research has shown that such a snooze function generating reminder notifications increases participant adherence [12]. As an additional alert, if a notification was waiting, it appeared as a heads-up notification (in a floating window) on each smartphone unlock.…”
Section: Ema Triggeringmentioning
confidence: 99%
“…Data are collected repeatedly over a certain period (often several days) and, more recently, through digital platforms like smartphone applications [9]. Several recent studies have shown the feasibility of using an EMA approach to investigate work stress experiences [10][11][12]. There are three main benefits to it compared to traditional epidemiological methods.…”
Section: Introductionmentioning
confidence: 99%
“…Because stress is part of life and cannot always be prevented, measuring stress-vulnerability factors (p.182) can also be useful in order to identify individuals at risk. For example, investigators may screen for neuroticism, hyper-vigilance, worrying, fearavoidance, and catastrophizing (Evers, Kraaimaat, Geenen, Jacobs, & Bijlsma, 2003;Evers, Gieler, Hasenbring, & Van Middendorp, 2014;Van Middendorp & Evers, 2016 To gain insight into the number, severity, and consequences of daily stressors, ecological momentary assessment (EMA) procedures can be used to measure acute stress (and potential consequences such as pain) levels by means of (electronic) diaries over a specific period of time, varying from several days up to a year (McIntyre et al, 2016;Shiffman, Stone, & Hufford, 2008). Technological advances such as EMA allow investigators to gauge specific thoughts, actions, and emotions that might provide detailed insight into the stress experience and its consequences.…”
Section: Stress Assessmentmentioning
confidence: 99%